Neutrophil to lymphocyte ratio in parkinson’s disease: a systematic review and meta-analysis - Samaneh Hosseini; Nasim Shafiabadi; Monireh Khanzadeh; Arshin Ghaedi; Raziyeh Ghorbanzadeh; Amir Azarhomayoun; Aida Bazrgar; Jalil Pezeshki; Hanieh Bazrafshan; Shokoufeh Khanzadeh (BMC Neurology, 2023)
Abstract Background The goal of this research was to explore the role of Neutrophil to lymphocyte ratio (NLR) in Parkinson’s disease (PD). Methods From inception to 4 June 2023, PubMed, Web of Science, and ProQuest were searched for papers comparing NLR in PD to healthy individuals. Standardized mean difference (SMD) with a confidence interval (CI) of 95% were calculated. Results A random-effect model revealed that PD patients had elevated NLR values compared to healthy individuals (SMD = 0.81, 95% CI = 0.47 to 1.14, P < 0.001). The results of subgroup analysis were as follows: (1) study design: We observed that patients with PD had higher levels of NLR than healthy controls in either retrospective (SMD = 1.12, 95% CI = 0.58 to 1.66, P < 0.001) or prospective (SMD = 0.43, 95% CI = 0.18 to 0.68, P = 0.001) studies. (2) Ethnicity: We noticed that individuals with PD had higher levels of NLR than healthy controls, whether they were East Asian (SMD = 0.93, 95% CI = 0.22 to 1.63, P = 0.010) or Caucasian (SMD = 0.75, 95% CI = 0.40 to 1.10, P < 0.001).The pooled sensitivity of NLR in the prediction of PD was 0.67 (95% CI = 0.61–0.73), and the pooled specificity was 0.66 (95% CI, 0.61–0.70). Conclusions Increased levels of NLR is highly related with the presence of PD. Further research is needed to determine the potential clinical benefits of this simple and low-cost biomarker in the PD diagnosis.